2012
DOI: 10.4304/tpls.2.4.688-698
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Textual Enhancement Formats Have Differential Effects on the Intake of English Subjunctive Mood?

Abstract: Abstract-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
3
5
1
Order By: Relevance
“…Therefor intensive focus on form was more effective than extensive focus on form. The findings of the study are in line with the findings of Chandler (2003), Farrokhi and Sattarpour (2012), Farahani and Sarkhosh (2012) and Rahimpour et al (2012) who found that intensive groups achieved highest rate of accuracy in their studies. However the findings of the present study ran against the findings of Saeb (2013) and Rouhi & Samiei (2010) who found that the degree of attention to form in written CF didn't have differential effect on learners' grammatical accuracy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefor intensive focus on form was more effective than extensive focus on form. The findings of the study are in line with the findings of Chandler (2003), Farrokhi and Sattarpour (2012), Farahani and Sarkhosh (2012) and Rahimpour et al (2012) who found that intensive groups achieved highest rate of accuracy in their studies. However the findings of the present study ran against the findings of Saeb (2013) and Rouhi & Samiei (2010) who found that the degree of attention to form in written CF didn't have differential effect on learners' grammatical accuracy.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study revealed that learners who received intensive form-focused instruction outperformed those who received extensive fromfocused instruction. Farahani and Sarkhosh (2012) investigated the effect of different formats of textual enhancement on 101 female EFL learners' intake of English conditional type II. The results indicated that intensive underlining format was more effective to induce the intake of target form.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one way to enhance noticing is through textual/visual Input-enhancement the main function of which is to draw learners' attention to linguistic forms by changing or modifying the physical appearance of target teaching points (Farahani & Sarkhosh, 2012). Write and Haleem (1991) consider visual material as one of the most important aspects of language teaching, but voice this concern that majority of teachers even experienced ones do not utilize visual materials to make their teaching more effective, communicative and interesting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Input enhancement aims at drawing learners' attention to linguistic form by modifying the appearance of target structure (Farahani & Sarkhosh, 2012). It is believed that external manipulation of input can influence intake and learning (Rashtchi & Gharanli, 2010).…”
Section: Introductionmentioning
confidence: 99%